2006
DOI: 10.1523/jneurosci.2589-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects on Fast Exocytosis Induced by Synaptotagmin 1 and 2 Isoforms and Abundance But Not by Phosphorylation

Abstract: Synaptotagmins comprise a large protein family, of which synaptotagmin 1 (Syt1) is a Ca 2ϩ sensor for fast exocytosis, and its close relative, synaptotagmin 2 (Syt2), is assumed to serve similar functions. Chromaffin cells express Syt1 but not Syt2. We compared secretion from chromaffin cells from Syt1 null mice overexpressing either Syt isoform. High time-resolution capacitance measurement showed that Syt1 null cells lack the exocytotic phase corresponding to the readily-releasable pool (RRP) of vesicles. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
89
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(107 citation statements)
references
References 73 publications
(102 reference statements)
16
89
2
Order By: Relevance
“…A previous study demonstrated that Syt T112A does not affect vesicle release in chromaffin cells (21). Our results underscore that, despite many similarities, key differences exist between the release machineries of chromaffin cells and synapses (see also refs.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…A previous study demonstrated that Syt T112A does not affect vesicle release in chromaffin cells (21). Our results underscore that, despite many similarities, key differences exist between the release machineries of chromaffin cells and synapses (see also refs.…”
Section: Discussionsupporting
confidence: 77%
“…The Syt1 homologs Syt7 and Syt12 contain similar phosphorylation sites in the linker between TM and C2A, and their phosphorylation potentiates Ca 2+ -induced vesicle fusion (19,20). Unexpectedly, a nonphosphorylatable Syt1 variant had no effect on vesicle fusion in mouse embryonic chromaffin cells (21). However, we previously observed only limited contribution of PKC in mouse embryonic chromaffin cells compared with adult bovine chromaffin cells and neurons (8,22), suggesting that the role of PKC may differ between model systems.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Indeed, it is striking that the only molecular manipulations that are known-or are likely based on published literature-to change the intracellular calcium-dependence of exocytosis triggering are mutations in synaptotagmins and SNAP-25 (Sorensen et al, 2003a;Wang et al, 2003;Chieregatti et al, 2004;Rhee et al, 2005;Wang et al, 2005;Nagy et al, 2006;Pang et al, 2006;Sorensen et al, 2006). In contrast, manipulations of proteins involved in exocytosis more often lead to changes in pool sizes and/or recruitment in the absence of a change in triggering: examples include tomosyn (Yizhar et al, 2004), Munc13 (Ashery et al, 2000), Munc18 (Voets et al, 2001;Gulyas-Kovacs et al, 2007), CAPS1 (Speidel et al, 2005), SV2 (Xu and Bajjalieh, 2001), Snapin (Tian et al, 2005), synaptobrevin (Borisovska et al, 2005), and ␣-SNAP/NSF .…”
Section: Discussionmentioning
confidence: 99%
“…Of the synaptotagmin family, synaptotagmin-2 exhibits the highest degree of homology with synaptotagmin-1. Indeed, synaptotagmin-2 can rescue synaptotagmin-1 deficiency, and its expression overlaps partially but not completely with synaptotagmin-1 (Geppert et al, 1994;Nagy et al, 2006).…”
mentioning
confidence: 99%